Concept of Islamic tourism in Malaysia - Laderlah, Siti Anis (2015)
Islamic tourism is a new field of study in Malaysia due to the fact that Malaysia is a unique and harmonious country consisting of many races of different faiths. The tourism industry being one of the national economic stimulus, has given the signs for the government to develop the Islamic Tourism Centre (ITC) Malaysia to promote a new strategy of Islamic tourism at the local and international levels. Islamic tourism sector covers a wide range of services; mostly in food and beverage, hospitality and leisure. However, the feature of Islamic tourism differs from the conventional tourism. Therefore, this study will identify the meaning of tourism from the Islamic perspectives from the assured sources, which are the Qur’an and the Sunnah. Definitely, Malaysia is a Muslim-majority country and Islamic tourism has been proclaimed as one of the niche areas because the demand from Muslim travelers is huge. Nevertheless, the understanding on Islamic tourism concept is still vague. Therefore, the objectives of this research are; to explore the meaning of Islamic tourism from the perspective of the Qur’an and the Sunnah, to uncover the classical jurist perception on Islamic tourism and to identify Islamic tourism practices in Malaysia. This study is a qualitative approach and the data is collected from previous literatures and in-depth interviews. This study will give a clear understanding on the concept of Islamic tourism to the public. Generally, Islamic tourism is the way of obedience to the Almighty, where the rules and obligations as the caliph in this world are fulfilled. The concept of Islamic tourism is related to social development, physical development, spiritual development,tourism as Ibadah, educational value, cultural value, religious value, Halal and Haram and ethics. The implementation of Islamic tourism concept is also seen to positive impacts to individuals, society, country and the whole wide world. This study shall be useful to become a guideline and reference to policy makers, service providers, tourists and academicians on Islamic tourism now that the industry has started to bloom in the recent years. Especially that Islamic tourism is much related with the halal concept and Malaysia is now going towards becoming a global halal-hub.